Inducing unconscious stress: cardiovascular activity in response to subliminal presentation of threatening and neutral words - Ploeg, Melanie M. van der; Koenig, Julian (Psychophysiology, 2017)
Stress-related cognitive processes may occur outside of awareness, here referred to as unconscious stress, and affect one's physiological state. Evidence supporting this idea would provide necessary clarification of the relationship between psychological stress and cardiovascular (CV) health problems. We tested the hypothesis that increases in mean arterial pressure (MAP) and total peripheral resistance (TPR) and decreases in heart rate variability (HRV) would be larger when threatening stimuli are presented outside of awareness, or subliminally, compared with neutral stimuli. Additionally, it was expected that trait worry and resting HRV, as common risk factors for CV disease, would moderate the effect. We presented a subliminal semantic priming paradigm to college students that were randomly assigned to the threat (n = 56) or neutral condition (n = 60) and assessed changes from baseline of MAP, TPR, and HRV. Level of trait worry was assessed with the Penn State Worry Questionnaire. The findings indicate that CV activity changed according to the hypothesized pattern: A higher MAP and TPR and a lower HRV in the threat condition compared with the neutral condition were found with practically meaningful effect sizes. However, these findings were only statistically significant for TPR. Furthermore, changes in CV activity were not moderated by trait worry or resting HRV. This is the first study to explicitly address the role of subliminally presented threat words on health-relevant outcome measures and suggests that unconscious stress can influence peripheral vascular resistance.
First published: 12 May 2017
Gesehen am 06.07.2018